2022
DOI: 10.1038/s41598-022-21353-7
|View full text |Cite
|
Sign up to set email alerts
|

Description of electroencephalographic data gathered using water-based medium-expansion foam as a depopulation method for nursery pigs

Abstract: The United States’ swine industry is under constant threat of foreign animal diseases, which may emerge without warning due to the globalized transportation networks moving people, animals, and products. Therefore, having disease control and elimination protocols in place prior to pathogen introduction is paramount for business continuity and economic recovery. During extraordinary circumstances, it may become necessary to depopulate large populations of animals, including swine, as a disease containment measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In a study that utilized EEG and external accelerometers in calves euthanized via captive bolt, unconsciousness occurred in 0 s, but convulsions lasted up to 13.8 min ( Collins et al, 2020 ). A study in WBF-depopulated nursery pigs demonstrated using EEG that unconsciousness occurred in 1.9 min and brain death in 3.1 min, supporting that time to COM is an overestimate of time to loss of consciousness ( Korenyi-Both et al, 2022 ). Therefore, it is likely that COM overestimates the time to unconsciousness in cattle and represents a conservative estimate of unconsciousness, which is the parameter most relevant to animal welfare during euthanasia or depopulation.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that utilized EEG and external accelerometers in calves euthanized via captive bolt, unconsciousness occurred in 0 s, but convulsions lasted up to 13.8 min ( Collins et al, 2020 ). A study in WBF-depopulated nursery pigs demonstrated using EEG that unconsciousness occurred in 1.9 min and brain death in 3.1 min, supporting that time to COM is an overestimate of time to loss of consciousness ( Korenyi-Both et al, 2022 ). Therefore, it is likely that COM overestimates the time to unconsciousness in cattle and represents a conservative estimate of unconsciousness, which is the parameter most relevant to animal welfare during euthanasia or depopulation.…”
Section: Discussionmentioning
confidence: 99%
“…Publications describing the use of water‐based foam, low and medium‐expansion foam or firefighting foam were not considered, because these were not representative of the method used and the cause of death was different (i.e. suffocation rather than anoxia), which may have different implications in terms of animal welfare, as in water‐based foam, the means of death is reported to be occlusion of the trachea (Korenyi‐Both et al., 2022). Any method designed to cause occlusion of the trachea would be equivalent to death by drowning or suffocation, which is not recognised as humane killing method in Council Regulation (EC) No 1099/2009 on the protection of animals at the time of killing.…”
Section: Methodsmentioning
confidence: 99%
“…(Recently reviewed by Arruda AG et al 62 ) Expansion gas-infused foams have been investigated. 63,64,65,66 A study by Lorbach et al 67 found that CO2 took an average of 202 sec for swine to stop moving -considerable better than N2 but not without its own issues.…”
Section: Animal Euthanasiamentioning
confidence: 99%